Surface-modified porous membranes with electrospun Nafion/PVA fibres for non-aqueous redox flow battery - Bang, Ho Seon; Kim, Dongyoung; Hwang, Seung Sang; Won, Jongok (ELSEVIER SCIENCE BV, 2016)
Selective layered membranes were fabricated using electrospun Nafion/(polyvinyl alcohol (PVA) fibres on porous membranes for non-aqueous vanadium redox flow battery applications (RFB). Porous Celgard 2400 polypropylene membranes were chosen as a porous support because they have a high ionic conductivity with excellent mechanical and dimensional stability in acetonitrile. The layers composed of the electrospun polyelectrolyte (Nafion) fibres on the porous support provide selectivity while maintaining the ion conductivity through the porous membrane. The membranes showed low vanadium acetylacetonate (V(acac)(3)) permeability in acetonitrile compared to that of the pristine Celgard porous membrane. The performance of a non-aqueous RFB based on V(acac)3 with electrospun Nafion/PVA fibres surface-modified porous membranes was evaluated and compared to that of Nafion 212 and Neosepta AHA membranes. Low coulombic and energy efficiencies of 49% and 32%, respectively, were obtained for pristine Celgard porous membranes, which are comparable to the values of Neosepta AHA membranes, and this low efficiency is due to the non-selectivity of the pore in the Celgard membrane. The values increase with the accumulated thickness of the electrospun Nafion/PVA fibres, with the coulombic and energy efficiencies reaching 69% and 50%, respectively, which are even higher than those of the Nafion 212 dense membranes. It is considered that porous supports contribute to the mechanical stability, and electrospun polyelectrolyte fibres accumulated on the surface reduce the crossover of the redox active species, resulting in the high performance of RFBs. This result implies that the electrospun modification of the mechanically stable porous membrane may enable the successful use of a non aqueous RFB for future energy storage systems. (C) 2016 Elsevier B.V. All rights reserved.